Algebraic approach to optimal clone selection applied in metagenomic projects - Cantão, Mauricio E.; De Araújo, Luciano V.; Lemos, Eliana G. M. [UNESP]; Ferreira, João E. (Association for Computing Machinery (ACM), 2010)
Due to the wide diversity of unknown organisms in the environment, 99% of them cannot be grown in traditional culture medium in laboratories. Therefore, metagenomics projects are proposed to study microbial communities present in the environment, from molecular techniques, especially the sequencing. Thereby, for the coming years it is expected an accumulation of sequences produced by these projects. Thus, the sequences produced by genomics and metagenomics projects present several challenges for the treatment, storing and analysis such as: the search for clones containing genes of interest. This work presents the OCI Metagenomics, which allows defines and manages dynamically the rules of clone selection in metagenomic libraries, thought an algebraic approach based on process algebra. Furthermore, a web interface was developed to allow researchers to easily create and execute their own rules to select clones in genomic sequence database. This software has been tested in metagenomic cosmid library and it was able to select clones containing genes of interest. Copyright 2010 ACM.
Keywords: Metagenomics; NPWS; Optimal clones; Process algebra; Scientific workflow; Algebraic approaches; Clone selection; Culture medium; Genomic sequence database; Genomics; Metagenomic libraries; Microbial communities; Molecular techniques; Process algebras; Scientific workflows; Web interface; Cloning; Genes; Management; Optimization; Soot blowers; Algebra